2013
DOI: 10.1038/cddis.2013.375
|View full text |Cite
|
Sign up to set email alerts
|

The AKT1/NF-kappaB/Notch1/PTEN axis has an important role in chemoresistance of gastric cancer cells

Abstract: The inherent resistance of tumors to DNA damage often limits the efficacy of chemotherapy. The aim of this work is to explore the potential mechanism for development of chemoresistance in gastric cancer. Our data revealed that AKT1 mRNA and protein expression were induced by doxorubicin (a chemotherapeutic agent); the doxorubicin-induced AKT1 expression and activation increased the binding of NF-kappaB on Notch1 DNA promoter and then promoted the Notch1 transcription and expression; enhanced expression of Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…S7a) 32 . The recruitment of JMJD3 and NF-κB p65 to the upstream region of Notch1 gene was investigated in HaCaT keratinocytes after scratching by a ChIP assay.…”
Section: Resultsmentioning
confidence: 99%
“…S7a) 32 . The recruitment of JMJD3 and NF-κB p65 to the upstream region of Notch1 gene was investigated in HaCaT keratinocytes after scratching by a ChIP assay.…”
Section: Resultsmentioning
confidence: 99%
“…The sections were developed using a 3,3 0 -diaminobenzidine tetrahydrochloride (DAB) substrate kit (ThermoScien-tific, MA) at room temperature for 1-5 min and then counterstained with hematoxylin. The intensity of the immunostaining was categorized as follows: no brown particle staining (0), light brown particle (1), moderate brown particle (2), and dark brown particle (3). The extent of immunostaining was quantified by counting the percentage of positive cells and classified into four groups: 0, less than 25% positive cells; 1, 25-50% positive cells; 2, 51-75% positive cells; and 3, more than 75% positive cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Numerous studies indicate that the development and progression of glioma arises via miss-regulation of many related genes such as p53, p21, Akt, Gli1, and PTEN [1][2][3][4][5][6]. However, the regulatory mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences have shown that Notch-1 is involved in the regulation of tumor cell growth, proliferation, apoptosis, metastasis and chemo- or radioresistance. Notch-1 was either reported as an oncogene [7] in some solid tumors, or reported as a tumor suppressor in other tumors [8]. The two different viewpoints were usually resulted from different types of tumors or different stages of tumors.…”
Section: Introductionmentioning
confidence: 99%